Synthesis, Biological Activities, and Crystal Structure of 1,2,4-Triazole Benzenesulfonamides - Sancak, Kemal; Kilinc, Gulsah Gul; Durak, Filiz; Ozsanli, Hanifi; Coruh, Ufuk; Barut, Burak (Elsevier, 2025)
In this study, firstly the ring closed reaction of hydrazine carboxylates (2) with 3-(2 aminoethyl) benzene sulfonamide (1) in a thermally controlled reaction afforded 4-(2-(3-alkyl/alkylaryl/aryl-5-oxo-1,5-dihydro-4H1,2,4-triazol-4-yl) ethyl) (3a-g) sulfonamide derivative 1,2,4-triazol-5-one compounds. The synthesized compounds were characterized using FT-IR, 1H-NMR and 13C-NMR spectra. In the second step, inhibition studies of acetylcholinesterase, butyrylcholinesterase alpha-glycosidase and tyrosinase were performed to determine the inhibitory properties of the compounds. In antimicrobial tests against 13 different microorganisms, it was determined that the compounds were selectively effective against the Bacillius Cereus pathogen. Antioxidant activity tests were performed in the part of the study, moderate radical scavenging properties were determined in all compounds except 3a and 3g. XRD analysis was performed to determine the structural parameters of the single crystal (3d) and to reveal the crystallographic structure information.
Özşanli, Hanifi/0009-0007-2645-902X; Sancak, Kemal/0000-0003-2064-9934; Gül Kilinç, Gülşah/0000-0002-9737-8477
Keywords: 4-Triazol-5-One; Sulfonamide; Enzyme Inhibition; Antioxidant Activity; X-Ray Diffraction; DFT